Analyzing 1937 AD Diplomacy and Cultural Exchange through the Hispano-Arab-Islamic Mecca Pilgrimage - Rosser, Pablo; Soler, Seila (Journal of Al-Tamaddun, 2024)
This research employs Interpretative Phenomenological Analysis (IPA) to delve into the historical interactions between Spain and the Arab-Islamic world during Franco's regime, with a focus on the 1937 pilgrimage to Mecca. This initiative exemplifies the use of cultural and religious diplomacy to enhance bilateral relations, revealing efforts to portray Spain as respectful of Islamic practices. By examining unpublished documents, including Francisco Limiñana's detailed planning of the pilgrimage, the study highlights the complexity of colonial and post-colonial relationships, blending cooperation and power dynamics. The analysis underscores the intertwining of Spain's internal policies with its external posture, aiming to bolster national identity and Franco's legitimacy. The findings challenge oversimplified narratives, offering a nuanced view of Western-Arab-Islamic interactions, essential for understanding contemporary challenges and fostering intercultural dialogue. Significantly, Limiñana's role transitioned from organizing the pilgrimage to becoming Spain's first ambassador to Saudi Arabia in 1956, illustrating the evolution of Spanish-Arab relations.